Teacher2Teacher |
Q&A #19812 |
From: Robert
To: Teacher2Teacher Public Discussion
Date: 2009090512:40:11
Subject: -x=2 is equal to x=-2
This is another approach.Given: -x=2 There is an implied 1 ahead of the x. Rewrite as: -1 * (x)= 2. Multiply both sides of the equation by -1, obtaining -1*(-1*(x))= -1*2. The result is +1(x)= -2, because -1*-1 must give a + 1. This is so because 1 multiplied must always equal itself. If anyone sees a fallacy here,please let me know. This may be related to the absolute value function, but I do not know how to make the connection. Robert
Post a reply to this message
Post a related public
discussion message
Ask Teacher2Teacher a new question
[Privacy Policy] [Terms of Use]
Math Forum Home ||
The Math Library ||
Quick Reference ||
Math Forum Search